Artificial hollows provide an effective short-term solution to the loss of natural nesting hollows for Carnaby's Cockatoo Calyptorhynchus latirostris. (May 2020) - Saunders, Denis A.; Dawson, Rick; Mawson, Peter R.; Cunningham, Ross B.
Abstract: The ecology of one breeding population of Carnaby's Cockatoo Calyptorhynchus latirostris has been studied at Coomallo Creek, Western Australia, since 1969. A wildfire destroyed breeding habitat in part of the study area and adjoining areas in late December 2009. An increase in the number of breeding attempts the following year suggested that hollows were probably limiting. From 2011, the number of hollows available to the cockatoos was increased by repairing derelict natural hollows and providing artificial hollows. By 2017, cockatoos had access to 87 natural and 68 artificial hollows the approximate dimensions of natural hollows. Artificial hollows were readily accepted, however there were significant differences in the probability of hollows being used due to location and land use type. Despite floor temperatures of black and white artificial hollows being warmer than those of natural hollows, there were no significant differences in the probability of hollow use, the probability of breeding failures, and nestling condition in either white or black artificial hollows or natural hollows. The number of breeding attempts rose from 52 in 2011 to 127 in 2016 indicating that management intervention was effective. Between 2011 and 2018, artificial hollows provided 45% of available hollows and 54% of breeding attempts were made in them. By 2018, the number of breeding attempts in the area was 112% higher than in 2011. Artificial hollows provide an excellent short-term solution to the continuing loss of natural hollows. However, without extensive re-establishment of breeding and foraging habitat, the future for Carnaby's Cockatoo is uncertain.